High anisotropic thermoelectric effect in palladium phosphide sulphide. Issue 9 (9th May 2017) - Kaur, Prabhjot; Chakraverty, Suvankar; Ganguli, Ashok Kumar; Bera, Chandan
Abstract: We have performed density functional theory (DFT) in combination with Boltzmann transport calculation to theoretically estimate the thermoelectric properties of ternary palladium pnictide chalcogenide, PdPS. A large thermopower, S, both for p‐type ( ∼ 345 μ V K − 1 ), and n‐type ( ∼ 335 μ V K − 1 ) PdPS at temperature, T = 300 K and carrier concentration, n = 10 20 cm − 3 has been observed. The orthorhombic PdPS has large anisotropic power factor in its three crystallographic directions, which may enable the designing of nanostructured thermoelectric devices in the temperature range of 300–800 K. We also show that thermal conductivity is considerably low ∼ 0.11 W ( mK ) − 1 in z ‐crystallographic direction of PdPS at 100 nm and 300 K. Our results imply that nanostructured PdPS can be a promising thermoelectric material.